EFEKTIVITAS METODE MENYANYI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS III MADRASAH IBTIDAIYAH - Nur Zakiyah; Fu’ad Arif Noor (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to find out how the application of the singing method in learning history, and its effectiveness in achieving learning outcomes of Islamic Cultural History in class III students of Madrasah Ibtidaiyah Tahassus (MIT) Ma'arif NU Pedan Klaten. While learning is less than optimal, it only views learning history as merely memorizing the years of events, names of figures, and events that occurred without taking lessons from it. Data collection techniques in this study through observation, interviews, tests, and documentation. This type of experimental research, the subjects used were class III students at MIT Ma'arif NU Pedan with a population of 31. Class III A was the control class and class III B was the experimental class. The results showed that by testing the hypothesis using the t test with a significance level of 5%, it was obtained = 0.648, while = 2.05. Because the average learning outcomes of students in learning using the singing method are better than the learning outcomes of students in conventional learning. Based on data obtained from the average final test score of the experimental class of 73.43 and the control group of 69.66. So that the singing method is effective for learning the history of Islamic culture in material on the history of the birth and genealogy of the Prophet Muhammad SAW.